Análise de um modelo de avaliação de desempenho econômico-financeiro na visão dos acionistas no mercado americano entre 2011 e 2014 - Gama, Fernando Alves (2016)
The main purpose of this research was analyze the relation between Liquidity, Profitability and Growth with the Shareholder return. The choice of these variables was based on a study demonstrating that companies in Turkey (as well as other studies of India, Australia and united States) that possessed good indicators in these variables showed high performance in different macroeconomic situations, either adverse or positive ones. And since another work demonstrated that, using factor analysis, these variables were discriminants and robust, a structural equation model was designed to be tested. Form the 6,579 companies initially selected, a sample of 609 American companies that had all financial information between 2011 and 2014 was formed. The main result is that every variable and the model itself presented robust results, what is interesting, mainly because of liquidity. Tests of quality of sampling (boostrap), size of firm control (revenue) and time shifting were performed. Even though the explicative power was low, since it is a reduced model of only three variables, the results of this research can encourage new studies by enlightening the importance of each of these variables in an efficient management in creating value.